An instrumental analysis of English vowels produced by Omanis - Hubais, Ali; Pillai, Stefanie (Journal of Modern Languages, 2017)
This article examines the pronunciation of English monophthongs by ten male Omani speakers. Vowel quality was measured according to the frequencies of the first (F1) and second formants (F2), and vowel duration was measured to investigate length contrasts between typical vowel pairs. The findings suggest that the vowels produced by the Omani speakers occupied a similar vowel space as British English vowels although individual vowels have different qualities. The vowels also showed a length contrast between vowel pairs with quality contrast being less distinctive. In addition, the vowels produced by the Omani speakers were similar to those produced by Arabic speakers from different regions, giving rise to the perception of an Arabic-accented English. Although the findings presented in this article are preliminary in nature, they contribute to the growing body of research on the production of vowels in different varieties of English.